Ready protease-catalyzed synthesis of carbohydrate-amino acid conjugates. - Boyer, V; Stanchev, M; Fairbanks, A; Davis, B (2001)
The protease-catalyzed synthesis of amino acid est-carbohydrate conjugates as glycopeptide analogues has been achieved in a highly regioselective and carbohydrate-specific manner using amino acid vinyl ester acyl donors and minimally or completely unprotected carbohydrate acyl acceptors, which together probed active sites of proteases to reveal yield efficiencies that are modulated by the carbohydrate C-2 substitutent, and that may be exploited to allow selective one-pot syntheses.